Studies on the fitness characteristics of wMel- and wAlbB-introgressed Aedes aegypti (Pud) lines in comparison with wMel- and wAlbB-transinfected Aedes aegypti (Aus) and wild-type Aedes aegypti (Pud) lines - Sadanandane, Candasamy; Gunasekaran, Kasinathan; Panneer, Devaraju; Subbarao, Sarala K.; Rahi, Manju; Vijayakumar, Balakrishnan; Athithan, Velan; Sakthivel, Annamalai; Dinesh, Sundaram; Jambulingam, Purushothaman (Frontiers in Microbiology, 2022)
Wolbachia, an intracellular maternally transmitted endosymbiont, has been shown to interfere with the replication of dengue virus in Aedes aegypti mosquitoes. The Wolbachia-transinfected Ae. aegypti has been currently released in many counties to test its effectiveness in preventing transmission of dengue virus. ICMR-Vector Control Research Centre in collaboration with Monash University, Australia has generated two new Wolbachia-introgressed Ae. aegypti Puducherry (Pud) lines via backcrossing Ae. aegypti females of Australian (Aus) strains, infected with wMel and wAlbB Wolbachia with wild type Ae. aegypti Puducherry (Pud) males. Wolbachia infections are known to induce a fitness cost and confer benefit on the host mosquito populations that will influence spread of the Wolbachia into native wild mosquito populations during the field release. Hence, the induced fitness cost or benefit/advantage in the two newly generated Ae. aegypti (Pud) lines was assessed in the laboratory in comparison to the wild type Ae. aegypti (Pud) strain. In addition, maternal transmission efficiency, induced cytoplasmic incompatibility and insecticide resistance status of the two (Pud) lines were determined to assess likely frequency of wMel and wAlbB infections in the native wild population after field invasion. The study shows that wMel and wAlbB infections did not induce any fitness cost on the two newly generated (Pud) lines. Rather, in terms of wing length, fecundity, egg hatch rate and adult survival, the Wolbachia introgression conferred fitness benefits on the (Pud) lines compared to uninfected Wolbachia free wild Ae. aegypti population. wMel and wAlbB exhibited a high maternal transmission (99-100%) and induced nearly complete (98-100%) cytoplasmic incompatibility. Both the (Pud) lines were resistant to delatamethrin, malathion, DDT and temephos and the level of resistance was almost same between the two lines as in the wild type. Overall, the stable association of wMel and wAlbB established with Ae. aegypti and the reproductive advantages of the (Pud) lines encourage a pilot release in the field for population replacement potential.